Differential Expression of miR‐4520a Associated With Pyrin Mutations in Familial Mediterranean Fever (FMF). Issue 6 (20th December 2016) - Latsoudis, Helen; Mashreghi, Mir‐Farzin; Grün, Joachim R.; Chang, Hyun‐Dong; Stuhlmüller, Bruno; Repa, Argyro; Gergiannaki, Irini; Kabouraki, Eleni; Vlachos, George S.; Häupl, Thomas; Radbruch, Andreas; Sidiropoulos, Prodromos; et al.
Abstract : Familial Mediterranean fever (FMF) is an autosomal recessive disease characterized by recurrent, acute, and self‐limiting attacks of fever. Mutations in MEFV gene encoding pyrin account for FMF, but the high number of heterozygote patients with typical symptoms of the disease has driven a number of alternative aetiopathogenic hypotheses. The MEFV gene was knocked down in human myelomonocytic cells that express endogenous pyrin to identify deregulated microRNAs (miRNAs). Microarray analyses revealed 29 significantly differentially expressed miRNAs implicated in pathways associated with cellular integrity and survival. Implementation of in silico gene network prediction algorithms and bioinformatics analyses showed that miR‐4520a is predicted to target genes implicated in autophagy through regulation of RHEB/mTOR signaling. Differential expression levels of RHEB were confirmed by luciferase reporter gene assays providing further evidence that is directly targeted by miR‐4520a. Although the relative expression levels of miR‐4520a were variable among FMF patients, the statistical expression of miR‐4520a was different between FMF mutation carriers and controls ( P  = 0.0061), indicating an association between miR‐4520a expression and MEFV mutations. Comparison between FMF patients bearing the M694V mutation, associated with severe disease, and healthy controls showed a significant increase in miR‐4520a expression levels ( P  = 0.00545). These data suggest that RHEB, the main activator of mTOR signaling, is a valid target of miR‐4520a with the relative expression levels of the latter being significantly deregulated in FMF patients and highly dependent on the presence of pyrin mutations, especially of the M694V type. These results suggest a role of deregulated autophagy in the pathogenesis of FMF. J. Cell. Physiol. 232: 1326–1336, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Familial Mediterranean fever (FMF) is an autosomal recessive disease characterized by recurrent, acute and self‐limiting attacks of fever. In the present study we presented for the first time results supporting a role of deregulated autophagy in the pathogenesis of FMF.